Nursing Homes' Competition and Distributional Implications when the Market is Two-Sided (2018)
We investigate the effect of competition in the nursing homes sector with a two-sided market approach. More precisely, we investigate the distributional implications across the three key actors involved (residents, nurses and nursing homes) that arise from the two-sidedness of the market. Within a Hotelling set up, nursing homes compete for residents and for nurses, who provide quality to residents, by setting residents price and nurses wage. Nurses are assumed altruistic and therefore motivated to provide quality. The market is two-sided because: i) a higher number of residents affects nurses workload, which affects their willingness to provide labour supply; and ii) a higher number of nurses affects residents quality through a better matching process and by relaxing nurses time constraints. Our key findings are that i) the two-sidedness of the market leads to higher wages for nurses, which makes the nurses better off; ii) this is then passed to residents in the form of higher prices, which makes residents worse off; iii) nursing homes profits are instead unaffected. In contrast, when nurses wages are regulated, the two-sidedness of the market implies a transfer between residents and nursing homes. When residents price are regulated, it implies a transfer between nurses and nursing homes. These results are robust to institutional settings which employ pay-for-performance schemes (that reward either nursing homes or nurses): the two-sidedness of the market is strengthened and residents are still worse off.